Proximity-Based Robust Event Detection in Wireless Sensor Networks - Chan-O Hong; Yoon-Hwa Choi (International Journal of Distributed Sensor Networks)
This paper presents a proximity-based event detection scheme for wireless sensor networks. It is a hybrid scheme in the sense that it takes advantage of both neighbor-based and cluster-based schemes in distinguishing events from false alarms due to faulty nodes. It gives more weights to alarms in closer proximity, while making event decisions at the cluster heads to reduce the communication overhead. The proposed scheme can effectively reduce false alarms while accurately detecting events even for a relatively small event region. Simulation results show that it greatly lessens the tradeoff between event detection accuracy and false alarm rate. Further improvements in performance can be made by removing identified faulty nodes from the network during normal operation.